2021
DOI: 10.1128/msystems.00104-21
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of SARS-CoV-2 Infection in the Upper Respiratory Tract and Its Relation to Breath Volatile Organic Compounds

Abstract: Among the many products of metabolic processes are volatile organic compounds (VOCs). In the airways, these volatile metabolites are emitted through breathing and thus are easily sampled for analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Our data also support the interest of focusing on the role of nutrition on exhaled BVM profiling at a time where this non-invasive procedure is proposed as an interesting tool to unravel metabolic and infectious diseases, like recently shown for Covid 19 infection in human. 50 This study supports the relevance of breath volatile metabolomic approach to unravel nutrients-gut microbiota-host interactions. Further experiments with different types of DF would allow to unravel the metabolomic signature of their interaction with the gut microbiome, knowing that the concepts of selective fermentation of DF is largely studied in vitro , but poorly assessed in vivo .…”
Section: Discussionsupporting
confidence: 78%
“…Our data also support the interest of focusing on the role of nutrition on exhaled BVM profiling at a time where this non-invasive procedure is proposed as an interesting tool to unravel metabolic and infectious diseases, like recently shown for Covid 19 infection in human. 50 This study supports the relevance of breath volatile metabolomic approach to unravel nutrients-gut microbiota-host interactions. Further experiments with different types of DF would allow to unravel the metabolomic signature of their interaction with the gut microbiome, knowing that the concepts of selective fermentation of DF is largely studied in vitro , but poorly assessed in vivo .…”
Section: Discussionsupporting
confidence: 78%
“…Carotenoid cleavage via carotenoid cleavage oxygenases (CCOs) and citral degradation via lyase were two important pathways of 6-MHO synthesis in the gut [ 54 , 55 ]. Notably, a few studies have reported statistically significant differences in bacterial diversity between the intestinal microbiomes of patients with COVID-19 and influenza and healthy controls [ 56 ]. Therefore, we believe that the gut microbiome plays an important role in regulating the volatile metabolome associated with immunization or infection.…”
Section: Resultsmentioning
confidence: 99%
“…VOCs are chemical compounds including gases, acids and alcohols released in body fluids for instance as a result of an infection in humans ( Sethi et al, 2013 ). Their composition is disease specific and was proven to be specific for SARS-CoV-2 ( Lichtenstein et al, 2021 , Wang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%